Growth Performance and Carcass Composition of 3 Crossbred Native Chicken Fed Diet Supplemented with Passion Fruit Peel - โต๊ะขวัญแก้ว จันทร์จิรา; Chanartaeparporn, Piphat (Princess of Naradhiwas University Journal, 2021)
The objective of this study was to investigate the growth performance and carcass quality of 3 crossbred native chicken fed supplemented with passion fruit peel. The 2 weeks aged of 150 three crossbred native chickens were randomly separated into 5 groups, 3 replications and 10 chickens per replication. Five groups were imposed by Completely Randomized Designs. They were fed supplemented with 0 (control), 2.5, 5.0, 7.5, and 10.0 percent of grinded passion fruit peel ad libitum for 12 weeks. After the experiment was finished, 2 chickens in each replication were slaughtered for collected carcass quality. The results showed that weight gain, average daily gain (ADG) and feed conversion ratio (FCR) of all groups were not statistically significant differences (P>0.05). Feed intake of the chicken fed supplemented at 10 % of passion fruit peel much more than the other groups (P<0.05). Carcass quality of all groups, live body weight, defeathered carcass weight, dressing carcass weight, defeathered carcass percentage, dressing percentage, and percent of each carcass parts were not statistically significant differences (P>0.05) except for wings, that 10 % fed supplemented with passion fruit peel was significantly higher than the other groups (P<0.05). So, 10 % fed supplemented with passion fruit peel had not affected to the growth performance and carcass quality in the 3 crossbred native chicken.